“There Must be Mouse Dirt with the Pepper”: A Lutheran Approach to Choosing Songs - Tönsing, Gertrud (Dialog, 2009)
This paper stems from my doctoral research on the question, “What is a good song?” It is a response to the Praise and Worship movement, which started within the charismatic churches, but also has spread to many mainline churches, including my own in South Africa. While I am supportive of much that is good in this movement, I am also critical of the content and theology of many of the songs. This paper focuses on what we as Lutherans can learn from our founder when it comes to choosing what and how to sing in our services.